Analisis Yuridis Kerangka Hukum Pencapaian Net Zero Emission Mengenai Perlindungan Hak atas Lingkungan Hidup terhadap Operasional PLTU Batubara di Indonesia - Muhammad Rahmadzani Hidayat (Media Hukum Indonesia (MHI), 2026)
Indonesia faces significant challenges in balancing energy needs with environmental protection. Coal-fired power plants remain the dominant energy source, yet they generate high emissions and pose public health risks. This study applies a normative-juridical method to analyze the effectiveness of the national legal framework in supporting the achievement of Net Zero Emissions (NZE) and protecting environmental rights. The results show that existing regulations support the energy transition, but implementation remains hampered by coal dominance, weak oversight, and minimal public participation. Legal strengthening, policy integration, and accountability are key to ensuring a sustainable and equitable energy transition.